THE INFLUENCE OF THE QUALITY OF GENERAL HEALTH CENTER UNIT ON PATIENT SATISFACTION IN THE PRIMARY HEALTH CENTERS OF SOUTH LAMPUNG REGENCY, LAMPUNG PROVINCE - Susi, Susilawati; Lubis, Samran; Lubis, Basyariah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The mismatch in the healthcare workforce ratio leads to suboptimal healthcare services in community health centers (Puskesmas). The quality of healthcare services needs to be evaluated from the perspective of both the institution and the patients, as interpreted through the community satisfaction index. This study utilized cluster randomized sampling. Data collection techniques included observation and questionnaires. The population of this study consisted of the number of outpatient visits in 7 (seven) medium-sized community health centers in South Lampung Regency in 2020, totaling 287,279 visits. The sample size for this study was 347 samples in each group. The study was conducted from February to March 2023. The aim of this research is to analyze the influence of healthcare service quality on patient satisfaction index in Community Health Centers in South Lampung Regency, focusing on the dimensions of Reliability, Assurance, Tangibles, Empathy, and Responsiveness (SERVQUAL). The results of this study showed that the Community Satisfaction Index (CSI) for healthcare services had a mean quality scale of 3.09, indicating a